Comparison of Test Statistics Using Simulated Data - รอดชื่น มานะชัย (KKU Science Journal, 2013)
This article considers the comparison of the test statistics under the test of size or level . The criteria of Cochran (1947), the criteria of Bradley (1978, cited in Tomarken and Serlin, 1986) and the criteria under hypothesis testing for are applied with distributions that are well approximated by a normal distribution and binomial distribution.